MINAT MAHASISWA JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG DALAM MENGIKUTI PROGRAM MAHASISWA WIRAUSAHA (PMW) - 511-520 , Joko Purnomo (CIVED, 2015)
Abstract   This study aims to reveal what the cause of the lack of student interest in participating in the Student Entrepreneurship Program. The population in this study were students of Department of Civil Engineering Prodi D3 and S1 year in 2011. This research is a quantitative descriptive. This research used simple random sampling from a population of 60 153 people. were collected using a questionnaire with Likert scale which consist of four answer choices. The number of statements in the questionnaire was 48 point statements. The finding of the research showed that of achievement of 61.92% is included in the low category. The main causes are the most affected by the lack of interest of students in participating PMW is the degree of attainment of information with 58.44%. Apart from other causes information student interest in participating in the PMW is the value of the degree of attainment of knowledge with 60.29%, emotions (feelings of pleasure) 62.91%, 63.06% willingness, and the latter can lead to lack of interest of students to PMW is attention to the degree of achievement of 63.26%. Keywords: Interest, Student Program, Entrepreneurship